Effect of exposure to ultraviolet light in the production of multi-sugar and poison for locally Alternaria alternata isolated fungi - Mohammed Ismail; Esam Soliman (College of Education for Pure Sciences, 2007)
Conidial spores of the fungus Alternaria alternata isolated from winter tomato fruits in Mosul were exposed to different periods of ultra violet light in order to test its effects on polysaccharide and toxin yield of the fungus. Production of polysaccharides were induced on the selective medium when exposed to (120) minutes ofU.V. light and reached(3.78 g/ 1) in shaken cultures .All mutated isolates inhibited toxin production.